2004
DOI: 10.1177/00343552040470040201
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Counselor Job Satisfaction and Consumer Satisfaction in Vocational Rehabilitation

Abstract: This study investigated the relationship between the job satisfaction of counselors employed by a state vocational rehabilitation (VR) agency and the satisfaction of their consumers with both the counselor and the overall VR experience. Multiple regression was used to determine whether facets of job satisfaction were related to consumers' satisfaction. Results indicated that job satisfaction was significantly related to consumer satisfaction and was able to account for a significant amount of variance in consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…Likewise, an individual who reported a low level of client satisfaction was less likely to be employed at the time of case closure. The resu Its provide support for previous research on the correlation between positive employment outcomes and high degrees of client satisfaction (Capella & Andrew, 2004;Kosciulek et aI., 1997;Schwab, Smith, & DiNitto, 1993). In particular, the results indicate a disparity between the two groups in terms of their perceptions of their employment readiness after completing the VR program.…”
Section: Discussionsupporting
confidence: 79%
“…Likewise, an individual who reported a low level of client satisfaction was less likely to be employed at the time of case closure. The resu Its provide support for previous research on the correlation between positive employment outcomes and high degrees of client satisfaction (Capella & Andrew, 2004;Kosciulek et aI., 1997;Schwab, Smith, & DiNitto, 1993). In particular, the results indicate a disparity between the two groups in terms of their perceptions of their employment readiness after completing the VR program.…”
Section: Discussionsupporting
confidence: 79%
“…Brown, Hohenshil and Brown (1998), in their study of school psychologists, found that subjects were dissatisfied with the policies and procedures of the school and the opportunities for advancement. Capella and Andrew (2004) investigated the job satisfaction of counselors and determined that opportunities for promotion had the lowest mean score on their job satisfaction scale. Kohout and Wicherski (1999) found that psychology doctoral graduates who were employed indicated chances for advancement on their current job did not contribute much to their job satisfaction.…”
Section: Facet Job Satisfactionmentioning
confidence: 99%
“…Steffen, Nystrom and O'Connor (1996) discovered a significant relationship between a nursing home employee's commitment to the organization and family members' perception of service quality. The importance of internal marketing in VR was recently demonstrated by Capella and Andrew (2004), who showed that DVR counselor job satisfaction of the work itself, opportunities for promotion and compensation were significantly and positively related to participant satisfaction. As discussed in the relationship marketing section, social bonds that grow between the counselor and the disabled individual are also expected to impact satisfaction with the VR program.…”
Section: Health Marketing Quarterlymentioning
confidence: 97%
“…Its achievement requires the development of strong internal and external relationships among all involved in the rehabilitation and employment process. Both relationship marketing and internal marketing provide the theoretical basis for understanding these relationships and how they impact the overall satisfaction of VR participants (Capella and Andrew, 2004). Because individuals with disabilities who participate in gainful employment have a higher level of subjective life satisfaction and well being compared to those who are not employed (Vestling, Tufvesson and Iwarsson, 2003), the goal of VR is to "facilitate maximum functioning and quality of life, encouraging independence and patient involvement" (Chachkes, 1999, p. 616).…”
Section: Disabilities Definedmentioning
confidence: 99%